Prediction of carbamazepine-succinic acid co-crystal dissolution in ethanolic solution using a computational molecular dynamic simulation technique : article - Pauzi, Noor Sazmira; Anuar, Nornizar; Yusop, Siti Nurul ‘Ain; Md Azmi, Nik Salwani (2018)
Co-crystallization process that comprise of APIs drug and co-crystal conformer (CCFs) is one of the method that is proven can improve the performance of the drugs in term of solubility, bioavailability, flow properties, thermal stability, and filterability [1]. In this study, co-crystal of Carbamazepine- Succinic acid (CBZ-SA) was used. The purpose of this study is to predict morphology of CBZ-SA cocrystal in vacuum and to access the dissolution behavior of CBZ-SA in ethanol solvent. The materials used in this study are (CBZ-SA) cocrystal and ethanol solvent while the method used is molecular dynamic simulation technique (theoretical method). An atomic charge calculation method was used to predict the morphology of the (CBZ-SA) cocrystal by using Dmol3 and MOPAC model. After the charged is calculated, the crystal structure was subjected to geometry optimization and then energy minimization by using the potential functions such as COMPASS, COMPASS26, COMPASS27, cvff, pcff, Universal, and Dreiding. Then, the morphology of the cocrystal was obtained. The simulated morphology of CBZ-SA co-crystals that use Dreiding force field resulted in elongated needle-like shape which shows similar shape with the experimental morphology demonstrated from previous research. For the assessment of dissolution behavior of CBZ-SA co-crystals in ethanol solvent, the mean square displacement (MSD) and radial distribution (RDF) were used to analyze the interaction between co-crystals and solvent molecules.